(untitled) - Stanley, Thomas (New York, 1975)
Contents: The following history consists of nineteen parts; the first treats of the seven sages or wise men of Greece, so famous in Antiquity; the others give us an ample account of the twelve different sects of philosophers, the lives of the most eminent professors, and the opinions held by them. The last treat of the Chaldaick philosophy, an abstruse and difficult subject, and which required no less learning than Mr. Stanley's to venture on it. Long out of print, this classic in the field of philosophy is now available once again from the Apocryphile Press
Keywords: Philosophy,Triết học; History,Lịch sử